Formación de híbridos de maíz de cruza múltiple partiendo de híbridos comerciales - Torres-Morales, Juan José; Chapa-Elizondo, José Alfredo; Martínez-Jaime, Oscar Alejandro; Bucio-Villalobos, Carlos Manuel (Acta Universitaria, 2011)
The aim of this research was getting information about thirty experimental hybrids of maize, all of them multiple crosses from commercial hybrids as parents. Hybrids were sown field on three locations: El Llanito, San Antonio and Marquez which belong to Irapuato, Gto., Mexico. Lattice 7 x 7 were used as experimental design and combined analysis and stability parameters models for comparing varieties through environments. Besides, seven characters were evaluated: plant height, ear height, ear length, percent of blow over, percent of double ear and grain yield. Results indicated the following: Response all maize genotypes is not similar across over environments and locations amongst themselves. In Fact multiple crosses as Leon x Tigre, Lince x Leon, 30G54 x Leon, 30G45 x Tigre y Aspros-948 x Tigre were stables genotypes for seven characters above all grain yield, however Lince x Tigre y DK-2002 x Leon had good response for not favourable conditions and favourable conditions. Commercial hybrids as Oso, Aspros-900, DK-2020, DK-2000, Bida-33, Bida-55 and DK-2002 result out standing for grain yield and were: 11.12 t/ha, 10.81 t/ha, 10.63 t/ha, 10.11 t/ha, 9.78 t/ha, 9.77 t/ha y 9.47 t/ha, whereas DK-2020 was defined as hybrid has good response for not favourables environments. The most important it indicates that DK-2002 x Leon hybrid was defined as good as the best hybrid: Oso, Aspros-900 and DK-2020. Finally, farmers can use this technology to produce seeds beginning with commercial hybrids seeds.